In Vitro Study to Evaluate the Best Conditions Highlighting the Antimicrobial Activity of Carum carvi Essential Oil on Human Pathogen Isolates in Formulations Against the Spread of Antibiotic Resistance - Mastrella, Carolina; Rizzo, Silvia; Vito, Maura Di; Garzoli, Stefania; Mercurio, Mattia Di; Mariotti, Melinda; La Sorda, Marilena; Zhiri, Abdesselam; Sanguinetti, Maurizio; Bugli, Francesca (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: In recent years, antimicrobial resistance has become a major threat to global health, and scientific research aiming to identify new therapeutic resources is a priority. Essential oils (EOs), obtained from spices belonging to the culinary tradition, like Carum carvi essential oil (CC-EO), are of great interest for their antimicrobial activity, but the methods used to evaluate their efficacy need to be standardized. The aims of this work were to evaluate the following: (i) the best microbiological in vitro test; (ii) the best surfactant; and (iii) the best microbiological target of CC-EO and its method of administration. Methods: CC-EO quality was evaluated using gas chromatography–mass spectrometry. Antimicrobial susceptibility testing with drugs currently in use was performed. Antimicrobial effectiveness against 70 clinical strains belonging to S. aureus, E. coli, E. faecalis, K. pneumoniae, P. aeruginosa, S. pyogenes, and C. albicans was evaluated. Two microbial tests (broth microdilution tests and disk diffusion), generally used in routine clinical practice, were compared. To choose the best vehicle, Tween80, DMSO, and ethanol were evaluated. The antimicrobial efficacy of vapors was assessed using a microatmosphere test. Results: The broth microdilution test is confirmed as the best in evaluating the antimicrobial activity of EOs. The most suitable EOs vehicle for antimicrobial testing was Tween80. CC-EO and its vapors were effective against GRAM+ and C. albicans strains, both sensible and resistant, and ineffective against GRAM−. Conclusions: In the future, it may be possible to include CC-EO in topical or spray formulations for the treatment of GRAM+ and C. albicans infections.